دراسة مؤشرات قياس الأداء في محطة حاويات اللاذقية الدولية - سائر صليبة (Tishreen University, 2019)
Performance indicators for container terminals are the primary attraction of container vessels. These are the most important standards that these terminals provide to their customers. The competition between these terminals is very strong to provide the best services and efficiency that reduces the time of ships on their berths and containers in their yards to the lowest time. This reflects an increase in productivity and reduction in storage costs, that is very important to the shipping agents, so it had to work on the continuous re-preparation of the yards and berths and transport equipment and cranes commensurate with rapid changes and the great development in the number of containers. The study focused on analyzing the performance levels of the main operating operations on the terminal's berths and in its different yards through a set of indicators and criteria that determine the optimal investment and utilization of the station's resources of infrastructure, equipment and mechanisms. تشكل مؤشرات الأداء لمحطات الحاويات عامل الجذب الأول لسفن الحاويات وهي المعايير الأكثر أهمية التي تقدمها هذه المحطات لعملائها، فكان التنافس فيما بينها على أشده من أجل تقديم أفضل الخدمات وبكفاءة تقلل زمن بقاء السفن على أرصفتها وزمن الحاويات في ساحاتها إلى أقل فترة زمنية ممكنة، الأمر الذي يعكس زيادة في الإنتاجية وخفض في تكاليف التشغيل والتخزين وهي من المؤشرات الهامة جداً لوكلاء الخطوط الملاحية، لذلك كان عليها العمل على إعادة التأهيل والتجهيز المستمر للساحات والأرصفة ومعدات النقل والتستيف والشحن والتفريغ بما يتناسب مع التغيرات السريعة والتطور الكبير في أعداد الحاويات. فقد تطرقت الدراسة إلى تحليل مستويات الأداء للعمليات التشغيلية الرئيسية على أرصفة المحطة وفي ساحاتها المختلفة وذلك من خلال مجموعة من المؤشرات والمعايير التي من شأئها تحديد مدى الاستثمار والاستخدام الأمثل لموارد المحطة من بنى تحتية ومعدات وآليات.